A család ereje: A házasságban élés és a nagycsaládos lét kapcsolata a jóllét különböző mutatóival - Andrea FERENCZI; Zsuzsanna KÖVI; Veronika MÉSZÁROS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Strength of the Family: Links between Marital Status, Large Family Structure, and Indicators of Well-Being. THEORETICAL BACKGROUND – Based on previous empirical findings, the relationship between family formation, the number of children, and subjective well-being cannot be considered unambiguous. This complex association is shaped by various individual and social factors. While having children may foster a sense of meaning in life and enrich individuals with emotionally fulfilling experiences, an increasing number of children may, in certain circumstances, strain the stability of family functioning. Regarding the positive consequences of parenthood, religiosity is frequently identified in the literature as a protective factor, and increasing attention has also been given to additional psychological resources – particularly social support and gratitude.